Загрози в мережі Blockchain - Фесенко, Д. О.; Караваєв, В. (ХНУРЕ, 2019)
Blockchain is a digital system that is based on model without a central storage. To design the system according to the requirements of blockchain, developers must take to attention rules on using such kind of system. The only system’s thread itself that will be implemented on the blockchain during development, will make your system much less robust, so to create a really goodsecured system developers should understand all threads in blockchain and to be possible to persist them
Keywords: Blockchain; атака; вразливість; децентралізація